2015
DOI: 10.1371/journal.pone.0123580
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Triacylglycerol Biosynthetic Pathway in Developing Seeds of Chia (Salvia hispanica L.): A Transcriptomic Approach

Abstract: Chia (Salvia hispanica L.), a member of the mint family (Lamiaceae), is a rediscovered crop with great importance in health and nutrition and is also the highest known terrestrial plant source of heart-healthy omega-3 fatty acid, alpha linolenic acid (ALA). At present, there is no public genomic information or database available for this crop, hindering research on its genetic improvement through genomics-assisted breeding programs. The first comprehensive analysis of the global transcriptome profile of develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
(43 reference statements)
2
27
0
Order By: Relevance
“…MAG is converted to DAG by MAG acyltransferase (MGAT) that transfers an acyl moiety from acyl-CoA to MAG. Finally, DAG is then acylated by DAG acyltransferase (DGAT) to produce TAG (Sreedhar, Priya, Sunny, Ram, & Malathi, 2015;Vijayaraj et al, 2012).…”
Section: Identified Proteins From Chia Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAG is converted to DAG by MAG acyltransferase (MGAT) that transfers an acyl moiety from acyl-CoA to MAG. Finally, DAG is then acylated by DAG acyltransferase (DGAT) to produce TAG (Sreedhar, Priya, Sunny, Ram, & Malathi, 2015;Vijayaraj et al, 2012).…”
Section: Identified Proteins From Chia Seedsmentioning
confidence: 99%
“…The MGAT can be soluble, as above, or associated with oleosin. In this case, MGAT has a role to form TAG that will be stored in oleosin (Sreedhar et al, 2015). Because of this, MGAT can have a role in preserving unsaturated fatty acids in plants, such as Ricinus communis, Brassica napus, and maize (Baud & Lepiniec, 2010).…”
Section: Identified Proteins From Chia Seedsmentioning
confidence: 99%
“…Besides perilla, flax ( Linum usitatissimum ), sacha inchi ( Plukenetia volubilis L. ), and chai ( Salvia hispanica L ., a member of mint family Lamiacease ) also contain high percentage of ALA in seed oil [ 14 ]. Seed transcriptome data of Chai [ 16 ] and sacha inchi ( Plukenetia volubilis L. ) [ 17 ] have been published, but a few genes contributing to the accumulation of ω-3 FA have been characterized for their expression profiles during seed development.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequences of their corresponding homologs taken from TAIR ( https://www.arabidopsis.org/ ) database served as a query for a TBLASTN search against assembled transcripts of S . hispanica [ 3 ]. Local blast (TBLASTN) was done using the software given in the following link ( https://www.blaststation.com/intl/en/blaststation2.php ).…”
Section: Methodsmentioning
confidence: 99%
“…The transcriptome analysis has been performed recently on the developing seeds of S . hispanica and different enzymes have been identified that are proposed to play a pivotal role in the flux of ALA into triacylglycerol (TAG) [ 3 ]. To further our understanding of biosynthetic pathway leading to the accumulation of ALA in TAG, gene expression analysis is an important tool.…”
Section: Introductionmentioning
confidence: 99%